SYSTEM OF CONTROL AND MANAGEMENT OF ACCESS ON THE BASIS OF ARDUINO MICROCONTROLLERS - N. V. Buzhinskaya; E. S. Vaseva; R. N. Iskandarov; N. V. Shubina (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the study is to select methods and means for the effective modernization of the security system existing in the enterprise.Method. It is proposed to improve the access control mode using the access control system based on ARDUINO microcontrollers. To highlight the functions of the system and the requirements for it were built UML-diagrams. On the basis of these diagrams, the balls have developed a schematic electrical diagram of the hardware of the system with an indication of all its elements. At the next stage, an algorithm was proposed for the operation of the hardware of the access control system. The implementation of a part of the algorithm for information exchange between the device and the information system is shown in the form of a sketch using the example of packet transmission over an Ethernet network using the TCP protocol. An intuitive interface has been developed for interaction between the access control system and the end user. The necessary information is stored in a database created in a Microsoft SQL Server environment.Result. The developed system was tested at the enterprise by means of sketches and a multimeter. Test results allow us to conclude that the system is ready for implementation. Conclusion. The article describes one of the methods for upgrading the existing access control system through a more user-friendly interface and the addition of entry/exit functions.Acknowledgments. The work was commissioned by the company LLC «Kalinin Baranchinsky Electromechanical Plant».